A study on creativity, gender, age and multiple intelligences in students of Compulsory Secondary Education in (Praxis Educativa, 2019)
In Education, it is important to know the potential of students to offer an educational response tailored to their needs. The objective of the article is to study the relationship between: creativity, gender, age and multiple intelligences. A quasi-experimental and correlational design was followed, applying a sample of 100 students of Compulsory Secondary Education (ESO), the RIBS Test of Runco, Plucker and Lim (2000-2001) for creativity and the Armstrong Multiple Intelligences Questionnaire (1999), along with age and gender. The results obtained verify that there are significant differences between creativity and multiple intelligences (IM) according to gender. And that there is a significant relationship between creativity and some of the multiple intelligences. As a conclusion, it is necessary to continue researching in order to offer an educational quality.
Keywords: creativity; age; gender; multiple intelligences; students.